RUSUNAWA INVESTMENT ANALYSIS IN TAMBAK WEDI DISTRICT, KENJERAN DISTRICT, SURABAYA CITY - Mawardianto, Hayadi Agus; Nugroho, Laksono Djoko; Muhammadun, Haris (Transpublika Publisher, 2024)
A total of 5,354 MBR individuals have applied to reside in Rusunawa and have remained on the waiting list until 2022. This has prompted the Surabaya City Government to provide Rusunawa, with one of them located in Tambak Wedi Village, Kenjeran District, Surabaya City. The objective of this research is to assess the viability of investing in the construction of Rusunawa Tambak Wedi from technical, market, and financial perspectives. The research methodology combines quantitative and qualitative approaches, utilizing primary and secondary data obtained previously. The technical feasibility analysis indicates that the construction of Rusunawa is deemed feasible, as it falls under the government's responsibility to address the housing needs of MBR individuals. The analysis considers factors such as the KDB space utilization intensity of 50%, KLB of 8 points, maximum building height of 100 meters, and KDH of > 10%. Furthermore, the market feasibility analysis reveals that 77.7% of the respondents, primarily from the MBR category, have expressed interest in residing in Rusunawa. Additionally, 69.9% of the respondents have stated their willingness to pay rent below Rp. 750,000 per month. Lastly, the financial feasibility analysis demonstrates that the Medium Rate Structure 1, Lower Rate Structure 1, and Lower Rate Structure 2 are considered feasible based on the NPV, IRR, BCR, and PP methods. However, the Medium Rate Structure 2 and Upper Rate Structure are deemed unfeasible.